Basic Education Teachers´ Valuation about the Courses of Continuous Formation - Aldo Bazán Ramírez; Doris Castellanos Simons; Gabriela Galván Zariñana; Laura Cruz Abarca (Universidad Autónoma de Madrid, 2016)
The aim of the present study was to identify the assessments of Morelos´teachers about the courses continuous formation received. The teachers were selected from different modalities and levels in Basic Education (Indigenous Education, General and Secondary Technical Education; TV-based Secondary schools; Preschool Education; Special Education and Encyclomedia Primary schools). Initially, 115 teachers completed a questionnaire with six dimensions: Satisfaction, Applicability, Motivation, Reflection, Relevance and Course Implementation. In the second stage, the opinions of 16 teachers selected from the former sample were examined using semi-structured interviews in order to deepen in their appraisals about the courses and its impact on their professional practice. Some important aspects identified were that the training courses meet only moderately teachers´ expectations and goals, presented a low correspondence between their contents and the needs of their everyday practice, and were considered as poorly related to the prior problems of their professional contexts.